Phylogenetically related, clinically different: Human papillomaviruses 6 and 11 variants distribution in genital warts and in laryngeal papillomatosis (2014)
ABSTRACT: Genital warts (GWs) and laryngeal papillomatosis (LP) are two usually benign pathologies related to infection with human papillomaviruses (HPVs), mainly HPV6 and HPV11. The aim of this work was to describe the genetic diversity of HPV6 and HPV11 isolates found in GWs and LPs, and to analyse the differential involvement of viral variants in either lesion. A total of 231 samples diagnosed as GWs (n = 198) or LP (n = 33) and caused by HPV6 or HPV11 monoinfections were analysed. The phylogenetic relationships of the retrieved viral sequences were explored. We have identified the long control region and the intergenic E2-L2 region as the two most variable regions in both HPV6 and HPV11 genomes. We have generated new HPV6 (n = 166) or HPV11 (n = 65) partial sequences from GWs and LPs lesions spanning both regions and studied them in the context of all available sequences of both types (final n = 412). Our results show a significant (p <0.01) differential presence of HPV6 variants among both pathologies, with HPV6 B variants being preferentially found in GW versus LP samples. No differential involvement of HPV11 variants was observed. Our findings suggest that different HPV6 variants may either show differential tropism or have different potential to induce lesions in different epithelia.